Equation 1) 3x = 9 - 6y
Equation 2) 3x + 8y = 9
Add 6y to both sides in equation #1.
1) 3x + 6y = 9
2) 3x + 8y = 9
Subtract equations from one another.
-2y = 0
Divide both sides by -2.
y = 0
Plug in 0 for y in the first equation.
3x = 9 - 6y
3x = 9 - 6(0)
Simplify.
3x = 9 - 0
Simplify.
3x = 9
Divide both sides by 3.
x = 3
So, x = 3, y = 0
~Hope I helped!~
Consider the puzzle:
"I have In mind a (secret) number. When I subtract 2/5 from this number I get 7. What is the number?"
To solve such puzzles we go backwards. We got 7 after we subtracted 2/5, so if we add 2/5 to 7, we get the secret number back.
Solving an equation is solving a puzzle about a secret number, which we call "x" instead of saying "something", all the time.
going backwards, means adding, if we subtracted, or dividing, if we multiplied.
So, to solve
, we just need to add 2/5 back to x:
to add 7 and 2/5, multiply 7 by 5/5
7+2/5=7.(5/5)+2/5=35/5+2/5=37/5
Thus x= 37/5
Answer:
6-(4*0.5)=h; h=4 in.
Step-by-step explanation:
Answer:
Always true
Step-by-step explanation:
14 + 3x – 7 = 7x + 7 – 4x
7 + 3x = 3x + 7